A peeling approach for integrated manufacturing of large monolayer h-BN crystals - Wang, R; Purdie, D; Fan, Y; Massabuau, F; Braeuninger-Weimer, P; Burton, O; Blume, R; Schloegl, R; Lombardo, A; Weatherup, R; Hofmann, S (American Chemical Society, 2019)
Hexagonal boron nitride (h-BN) is the only known material aside from graphite with a structure composed of simple, stable, noncorrugated atomically thin layers. While historically used as a lubricant in powder form, h-BN layers have become particularly attractive as an ultimately thin insulator, barrier, or encapsulant. Practically all emerging electronic and photonic device concepts currently rely on h-BN exfoliated from small bulk crystallites, which limits device dimensions and process scalability. We here focus on a systematic understanding of Pt-catalyzed h-BN crystal formation, in order to address this integration challenge for monolayer h-BN via an integrated chemical vapor deposition (CVD) process that enables h-BN crystal domain sizes exceeding 0.5 mm and a merged, continuous layer in a growth time of less than 45 min. The process makes use of commercial, reusable Pt foils and allows a delamination process for easy and clean h-BN layer transfer. We demonstrate sequential pick-up for the assembly of graphene/h-BN heterostructures with atomic layer precision, while minimizing interfacial contamination. The approach can be readily combined with other layered materials and enables the integration of CVD h-BN into high-quality, reliable 2D material device layer stacks.